Політична безпека України: стан та тенденції розвитку - Шемчук Андрій Володимирович (My University, 2023)
У дисертації вирішено актуальне наукове завдання, яке полягає у визначенні й аналізі стану та тенденцій розвитку політичної безпеки України та розробленні практичних рекомендацій органам публічної влади з їх використання з урахуванням існуючого стану в державі та світових тенденцій. Визначено ступінь розроблення наукової проблеми у політології і споріднених науках (публічне управління, економіка, право, воєнна справа); уточнено понятійно-категорійний апарат дослідження проблеми політичної безпеки України шляхом розмежування сутності понять «національна безпека» та «політична безпека»; визначено й охарактеризовано складові елементи політичної безпеки, її основні суб’єкти у системі публічної влади (президент, парламент, уряд); охарактеризовано стан забезпечення політичної безпеки України та провідних демократичних країн світу (США, Великобританія, Франція, Німеччина, Польща). Ключові слова: безпека, політична безпека, національна безпека, інформаційна безпека, політична система, парламент, гібридна війна, глобалізація, національні інтереси, публічна влада, політична влада.

The dissertation solves an actual scientific task, which consists in determining and analyzing the state and trends in the development of the political security of Ukraine and developing practical recommendations for public authorities on their use, taking into account the current state in the country and world trends. The degree of development of a scientific problem in political science and related sciences (public administration, economics, law, military affairs) is determined; the conceptual and categorical apparatus of the study of the problem of political security of Ukraine was clarified by distinguishing the essence of the concepts "national security" and "political security"; the constituent elements of political security, its main subjects in the system of public power (president, parliament, government) are defined and characterized; the state of ensuring political security of Ukraine and leading democratic countries of the world (USA, Great Britain, France, Germany, Poland) is characterized. Keywords: security, political security, national security, information security, political system, parliament, hybrid warfare, globalization, national interest, public power, political power.
Political security of Ukraine: the state and trends of development